ANALISIS KONSEPSI SISWA KONSEP DINAMIKA GERAK - Hendri Saputra (Jurnal Pendidikan Fisika dan Sains, 2018)
Abstract This research is a kind of qualitative descriptive research that aims to determine the level of misconception and understanding of students' concepts on the subject of motion dynamics in one of the State High Schools in West Aceh District Day. This study was conducted on 40 students of class XII majoring in Natural Sciences with sampling techniques carried out by purposive random. Data retrieval is done by means of diagnostic tests and interviews, to distinguish students who experience misconceptions, misconceptions, and concepts that are in accordance with scientific concepts used the CRI (Certain Respondent Index) method. The results showed that the average level of physics misconception of students in the concept of style was 41.64%, 18.36% answers were in accordance with scientific concepts, and as many as 40% of students lacked knowledge. From the results of the study it can be said that the average level of physical misconception of students is high compared to the answers of students who answer questions according to scientific concepts. The high percentage of students who experience misconceptions and students who lack knowledge shows that students' conceptual understanding is still very low. It is expected that the teachers and lecturers can analyze the students' initial conception so that misconceptions can be overcome from the beginning. Kata kunci: Miskonsepsi, Dinamika Gerak, Certain Responden Index)